ANALISIS HUKUM PENJUALAN HARTA GONO-GINI TANPA PERSETUJUAN ISTRI (STUDI KASUS PUTUSAN No.1684/Pdt.G/2019/PA.Mks): LEGAL ANALYSIS OF GONO-GINI PROPERTY SALES WITHOUT WIFE AGREEMENT (CASE STUDY DECISION No.1684 / Pdt.G / 2019 / PA.Mks) - Arbillah, Asriani; Santing, Waspada; Taba, Hamzah (Clavia, 2021)
This research was conducted at the Class 1A Makassar Religious Court, with the aim of finding out what underlies the husband selling his property without the wife's consent and knowing the judge's consideration so as to grant the wife's lawsuit in decision No.1684 / Pdt.G / 2019 / PA.Mks. This research is a normative legal research with a focus on empirical juridical studies. The results of this study indicate that the husband sold the gono-gini property without the wife's consent, because the joint assets or property generated during the marriage between the plaintiff and the defendant have been deemed to be divided between each party. However, the panel of judges did not agree with the agreement they made because it was unclear which one belonged to the plaintiff and which one belonged to the defendant so that the assets were determined based on the facts in court, namely the testimony of the witnesses. This became the judge's consideration in deciding case Number 1684 / Pdt G / 2019 / PA.Mks, granted part of the Plaintiff's claim because the panel had examined the letter of agreement made by the Plaintiff and Defendant, but the peace agreement letter was not clear in detail or in full regarding the assets of the Plaintiff and Defendant, which where the joint assets that are part of the Plaintiff and which are part of the Defendant, so that the panel assesses what the defendant argues that the shared assets between the Plaintiff and the Defendant have been divided is not proven but has not been divided between the Plaintiff and the Defendant, so that the panel of judges agrees that The Plaintiff's claim in this case is the Defendant's Wife.